2018
DOI: 10.3389/fchem.2018.00359
|View full text |Cite
|
Sign up to set email alerts
|

Advantage of a Narrow Spectrum Host Defense (Antimicrobial) Peptide Over a Broad Spectrum Analog in Preclinical Drug Development

Abstract: The APO-type proline-arginine-rich host defense peptides exhibit potent in vitro killing parameters against Enterobacteriaceae but not to other bacteria. Because of the excellent in vivo properties against systemic and local infections, attempts are regularly made to further improve the activity spectrum. A C-terminal hydrazide analog of the Chex1-Arg20 amide (ARV-1502) shows somewhat improved minimal inhibitory concentration against Moraxellaceae. Here we compared the activity of the two peptides as well as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…How to design AMPs with systemic in vivo efficacy is not clear. We found here 10,20,30,40,50,60,70,80,90, and 100 on the x axis of the plot. The sum of the averaged R% and K% from each bin is represented by the y axis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…How to design AMPs with systemic in vivo efficacy is not clear. We found here 10,20,30,40,50,60,70,80,90, and 100 on the x axis of the plot. The sum of the averaged R% and K% from each bin is represented by the y axis.…”
Section: Discussionmentioning
confidence: 75%
“…Additional positive charges might have facilitated peptide binding to host factors in vivo, rendering them unavailable for bacterial killing. In contrast, proline-rich peptides with high positive charges but low hydrophobic amino acids may also be less favorable to bind to multiple host factors, yielding an alternative design for in vivo efficacy against Gramnegative pathogens (40)(41)(42). Collectively, these results define two biased amino acid compositions for designing narrow-spectrum peptides with systemic in vivo efficacy: low cationic databasedesigned peptides against Gram-positive pathogens and low hydrophobic proline-rich peptides against Gram-negative pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ARV-1502 is active against a broad range of MDR Gram-negative bacterial species, including A. baumannii, P. aeruginosa, E. coli, and K. pneumoniae [18,19]. For instance, the peptide showed inhibitory activity on the growth of E. coli and K. pneumoniae strains with MIC values of 6 and 2 μg/ml, respectively [17,20].…”
Section: Discussionmentioning
confidence: 99%
“…including pyrrochorrycins [ 386 , 387 ], apeadicins [ 388 , 389 ], and oncocins [ 390 ]. Some of them are in a preclinical stage [ 391 , 392 ]. All of these are narrow spectral AMPs.…”
Section: The Efforts To Discover Omnipotent (“Jolly Joker”) Antibimentioning
confidence: 99%
“…All of these are narrow spectral AMPs. Some were more efficient in vivo than in vitro, supposedly due to cooperation with the innate immune system of the host to be protected [ 376 , 386 , 387 , 388 , 389 , 390 , 391 , 392 ].…”
Section: The Efforts To Discover Omnipotent (“Jolly Joker”) Antibimentioning
confidence: 99%